The Effects of Selected Sesquiterpenes from Myrica rubra Essential Oil on the Efficacy of Doxorubicin in Sensitive and Resistant Cancer Cell Lines - Ambrož, Martin; Matoušková, Petra; Skarka, Adam; Zajdlová, Martina; Žáková, Kateřina; Skálová, Lenka (Molecules (Basel, Switzerland), 2017)
β-caryophyllene oxide (CAO), α-humulene (HUM), trans-nerolidol (NER) and valencene (VAL) are constituents of the essential oil of Myrica rubra (MEO), which has significant antiproliferative effect in various cancer cell lines. In the present study, we compared the antiproliferative effect of these sesquiterpenes alone and in combination with the cytostatic drug doxorubicin (DOX) in cancer cell lines with different sensitivity to DOX. Two ovarian cancer cell lines (sensitive A2780 and partly resistant SKOV3) and two lymphoblast cancer cell lines (sensitive CCRF/CEM and completely resistant CEM/ADR) were used. The observed effects varied among sesquiterpenes and also differed in individual cell lines, with only VAL being effective in all the cell lines. A strong synergism of DOX with NER was found in the A2780 cells, while DOX acted synergistically with HUM and CAO in the SKOV3 cells. In the CCRF/CEM cells, a synergism of DOX with CAO and NER was observed. In resistant CEM/ADR cells, sesquiterpenes did not increase DOX efficacy, although they significantly increased accumulation of DOX (up to 10-times) and rhodamine-123 (substrate of efflux transporter ABCB1) within cancer cells. In conclusion, the tested sesquiterpenes were able to improve DOX efficacy in the sensitive and partly resistant cancer cells, but not in cells completely resistant to DOX.
Keywords: Polycyclic Sesquiterpenes; nádorové buněčné linie; Doxorubicin; drug resistance; drug combinations; Sesquiterpenes; Adriamycin; Drug Therapy, Combination; akutní lymfatická leukemie; monocyklické seskviterpeny; mnohočetná léková rezistence; Drug Synergism; Cell Proliferation; Cell Line, Tumor; Monocyclic Sesquiterpenes; Drug Resistance, Multiple; polycyklické seskviterpeny; synergismus léků; doxorubicin; kombinovaná farmakoterapie; Humans; Oils, Volatile; terpenes; viabilita buněk; Cell Survival; ABCB1 transporter; oleje prchavé; proliferace buněk; seskviterpeny; Myrica; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé